PENERAPAN SIMPLE DEBATE SEBAGAI ASESMEN AUTENTIK UNTUK MENGEVALUASI KEMAMPUAN MEMBERIKAN SARAN DAN TANGGAPAN SISWA KELAS V SEKOLAH DASAR - Ni Wayan Nik Sri Artini; Ida Bagus Putrayasa; Ni Ketut Desia Tristiantari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The evaluation process in the modern curriculum requires a shift from traditional test-based assessments to authentic assessments that can measure students' oral competencies in depth. In practice, the ability to express opinions, especially in giving advice and responses verbally, is still a challenge for elementary school students. This study aims to analyse the implementation of a simple debate method as a form of authentic assessment in evaluating the ability to give advice and responses among fifth-grade elementary students. This study is a descriptive qualitative research with 15 fifth-grade students as subjects. Data were collected through participatory observation during the debate process, in-depth interviews with educators, and document studies such as performance assessment rubrics. The findings indicate that the implementation of simple debates is proven effective as an authentic assessment tool.